Green Synthesis of Lead Sulphide Nanoparticles for High-Efficiency Perovskite Solar Cell Applications - Islam M.A.; Sarkar D.K.; Shahinuzzaman M.; Wahab Y.A.; Khandaker M.U.; Tamam N.; Sulieman A.; Amin N.; Akhtaruzzaman M. (MDPI, 2023)
In this study, lead sulfide (PbS) nanoparticles were synthesized by the chemical precipitation method using Aloe Vera extract with PbCl2 and Thiourea (H2N-CS-NH2). The synthesized nanoparticles have been investigated using x-ray diffraction (XRD), UV-Vis, energy-dispersive x-ray spectroscopy (EDX), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRD and TEM results confirm that the films are in the cubic phase. The crystallite size, lattice constant, micro-strain, dislocation density, optical bandgap, etc. have been determined using XRD and UV-Vis for investigating the quality of prepared nanoparticles. The possible application of these synthesized nanoparticles in the solar cells was investigated by fabricating the thin films on an FTO-coated and bare glass substrate. The properties of nanoparticles were found to be nearly retained in the film state as well. The experimentally found properties of thin films have been implemented for perovskite solar cell simulation and current-voltage and capacitance-voltage characteristics have been investigated. The simulation results showed that PbS nanoparticles could be a potential hole transport layer for high-efficiency perovskite solar cell applications. 2022 by the authors. Licensee MDPI, Basel, Switzerland.